Change of Discourse Type in a Social Activity - Dr. Shahzada Qaisar; Dr. Maria Shiraz (Research Journal of Social Sciences and Economics Review, 2020)
In this study, we propose classroom discourse as a dynamic activity whereby the discourse shifts from one mode to another within one social activity when students are involved to complete the task. The data for this study consisted of audio and video-recordings of the sessions. The analysis transcribed verbal and non-verbal behaviors of the students emerging during social activity. In the analysis, a transcript of one whole episode was taken from a larger study of the data set to inform about the discourse type used by the students during the social activity. The purpose of selecting one episode was to show the change in different types of discourse during a session. The finding of the study implies that in the context of social activity exploratory type discourse is required for learning. This study agrees with the general genetic law of cultural development that links the social, psychological, and cultural aspects during collaborative activities.